2011
DOI: 10.1107/s0907444911028198
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of human glioma pathogenesis-related protein 1

Abstract: Human glioma pathogenesis-related protein 1 (GLIPR1) is a membrane protein that is highly upregulated in brain cancers but is barely detectable in normal brain tissue. GLIPR1 is composed of a signal peptide that directs its secretion, a conserved cysteine-rich CAP (cysteine-rich secretory proteins, antigen 5 and pathogenesis-related 1 proteins) domain and a transmembrane domain. GLIPR1 is currently being investigated as a candidate for prostate cancer gene therapy and for glioblastoma targeted therapy. Crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 39 publications
5
48
0
Order By: Relevance
“…According to previous studies, after the translocation of the GLIPR1 (GLI pathogenesis-related 1) protein to the cell surface, the soluble N-terminal domain of the molecule is exposed to the extracellular space, which can lead to invasion [48,49]. In the present study, gain of the GLIPR1 gene was observed specifically in invasive cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…According to previous studies, after the translocation of the GLIPR1 (GLI pathogenesis-related 1) protein to the cell surface, the soluble N-terminal domain of the molecule is exposed to the extracellular space, which can lead to invasion [48,49]. In the present study, gain of the GLIPR1 gene was observed specifically in invasive cell lines.…”
Section: Discussionsupporting
confidence: 59%
“…We confirm that it is a glycoprotein, most likely at the predicted glycosylation site at asparagine 92 (5), which is shown by homology modeling of GLIPR1 to be on the surface of the protein (data not shown). Glycosylation was also seen in the recent expression and structural studies by Asojo and co-workers (23, 24). GLIPR1 is translocated to the cell surface where its soluble N-terminal domain will be exposed to the extracellular space.…”
Section: Discussionmentioning
confidence: 64%
“…Homology-based modelling for the cone snail (Conus textile) Tex31 (Milne et al, 2003) and human GAPR-1 (Serrano et al, 2004) proteins suggested a 'catalytic triad' consisting of serine (Ser)-73 with Glu-98/His-117 (or Glu-77/His-72) within the largest cavity in the PR-1 fold, which is reminiscent of that of serine proteases, but none of these PR-1like proteins has been confirmed to possess protease activity. Recent studies in human/animal systems have suggested 'novel' functions for PR-1-like proteins based on several newly identified properties, including coordination with divalent metal ions, such as Zn 2+ (Asojo et al, 2011;Wang et al, 2010), and binding to negatively charged membrane-associated lipids (van Galen et al, 2012) or certain fatty acid-derived lipid signalling molecules, such as leukotrienes (Xu et al, 2012). The importance of these unusual features in specific physiological processes has not been well established.…”
Section: Introductionmentioning
confidence: 99%